Pendidikan Rabbani dalam Keluarga Perspektif Sayyid Muhammad Bin Alawi Al-Maliki - Huda, Khoirul (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2024)
This study examines the concept of robbani education in the family from the perspective of Sayyid Muhammad Bin Alawi Al-Maliki and how to apply the concept of robbani education in Islamic families. By using library research, the primary data sources are Adabul Islam fi nidzom al-usroh and the book At-tahliyah wa at-targhib fi at-tarbiyah wa at-tahdzib. The results of the analysis show that rabbani education from the perspective of Sayyid Muhammad bin Alawi Al-Maliki can be achieved with the following indicators; 1) Aqidah/Faith; 2) Morals; 3) Knowledge; 4) Leadership; 5) Social community; 6) Indicator of Keeping Secrets; 7) Nationalism; 8) Deliberation/democracy; 9) Discipline